2014
DOI: 10.1002/chir.22365
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Circular Dichroism of Porphyrin Lanthanide M3+ Complexes

Abstract: Lanthanide complexes exhibit interesting spectroscopic properties yielding many applications as imaging probes, natural chirality amplifiers, and therapeutic agents. However, many properties are not fully understood yet. Therefore, we applied magnetic circular dichroism (MCD) spectroscopy, which provides enhanced information about the underlying electronic structure to a series of lanthanide compounds. The metals in the M(3+) state included Y, La, Eu, Tb, Dy, Ho, Er, Tm, Yb, and Lu; the spectra were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…[4][5][6][7] However, the development of molecular biologically relevant probes based on lanthanides is not straightforward. For example, many europium(III) complexes decompose in the aqueous environment 8 or the luminescence in water solutions is strongly affected by interaction with the O-H groups. The Na 3 [Eu(DPA) 3 ] complex (Scheme 1) used here and similar tris-dipicolinate (DPA) complexes of lanthanides appear to be more universal because they are stable also in water.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] However, the development of molecular biologically relevant probes based on lanthanides is not straightforward. For example, many europium(III) complexes decompose in the aqueous environment 8 or the luminescence in water solutions is strongly affected by interaction with the O-H groups. The Na 3 [Eu(DPA) 3 ] complex (Scheme 1) used here and similar tris-dipicolinate (DPA) complexes of lanthanides appear to be more universal because they are stable also in water.…”
Section: Introductionmentioning
confidence: 99%
“…While up to now we focused on one‐photon absorption (OPA) and emission, the model PESs described in the previous sections can be used, in combination with TD‐DFT data, to simulate many other achiral and chiral, linear and nonlinear spectroscopies. This includes Electronic Circular Dichroism (ECD), Magnetic Circular Dichroism (MCD), Circularly Polarized Luminescence (CPL), Near Edge X‐ray Absorption Fine Structure (NEXAFS), Two‐Photon Absorption (TPA), and Two‐Photon Circular Dichroism (TPCD). Going in further detail, for nonlinear processes some additional approximations are required in order to write the spectra in a form equivalent to Eqs or .…”
Section: Illustrationsmentioning
confidence: 99%
“…For example, the coordinate‐space grid may introduce a dependence on the origin . Recently, we found that the sum over states (SOS) approach provides a very efficient and accurate way of generating MCD spectra when the electronic excited states obtained from TDDFT computations are used . In test computations, we associated the Kohn–Sham determinant (very close to the Hartree–Fock one) with molecular ground state, and spin‐adapted TDDFT single excitations with excited electronic states.…”
Section: Introductionmentioning
confidence: 99%